The Relationship between Anxiety and Pain in Infusion Procedures: Implications for Children's Hospital Care - Megasari, Anis Laela; Wulandari, Ika Subekti; Maula, Sheyla Najwatul; Yusviputri, Nayla Asri (Global Health Science Group, 2024)
Insertion of an IV is a medical procedure that is often performed on children in hospitals. This procedure often causes anxiety and pain which can affect the child's comfort and healing process. Objective: This study aims to analyze the relationship between anxiety levels and the intensity of pain felt by children when installing an IV. Methods: The research method used is quantitative with a cross-sectional approach. The sampling technique uses purposive sampling by paying attention to inclusion and exclusion criteria. The total number of respondents in this study was 60 people. Data was collected through an anxiety questionnaire using the facial image scale (FIS) and a pain scale using the Wong Baker Face questionnaire. These two questionnaires were filled out by the child before and after the infusion procedure. Results: The results of data analysis showed that there was a significant positive correlation between the level of anxiety and the intensity of pain felt by children (r=0.49, p<0.05). Conclusions: The results of this study show that the higher the child's anxiety before the infusion procedure, the higher the pain intensity felt. This research suggests the importance of psychological intervention to reduce anxiety in children before the infusion procedure in order to reduce pain and increase the child's comfort during hospital treatment.